Evaluating changes in treeline position and land surface phenology in Sikkim Himalaya. Issue 5 (3rd April 2020) - Prakash Singh, Chandra; Mohapatra, Jakesh; Pandya, Himanshu A.; Gajmer, Bandan; Sharma, Narpati; Shrestha, Dhiren G.
Abstract: Mountain ecosystems of the Himalaya have warmed more rapidly in recent decades than other areas of the globe. Landscape-level delineation of treeline position and its dynamics can give insight regarding climatic variability. Landsat-2 Multispectral Scanner (MSS), Resourcesat-2 Linear Imaging Self Scanning Sensor (LISS-III) and National Oceanic and Atmospheric Administration- Advanced Very High Resolution Radiometer (NOAA-AVHRR) derived normalized difference vegetation index (NDVI) was used to study the long-term treeline dynamics. The treeline has shifted vertically 301 ± 66 m upward in 37 years at a rate of c . 81 m decade −1 . The minimum air temperature has increased at a rate of 0.3 °C decade −1 ( p  < 0.001) depicting the favourable scenario for treeline growth in this temperature limited ecosystem. The annual cumulative precipitation has decreased at a rate of 206.5 mm decade −1 . The length of growing season (LOS) has increased and the start (SOS) and end of growing season (EOS) has got earlier in the 1977 treeline. The elevation shifts and phenological changes of the treeline were observed in the warming scenario.